Reliability evaluation of scalable complex networks through delta-star conversion - Al-Khateeb, Wajdi Fawzi Mohammed; Al-Irhayim, Sufyan; Al-Khateeb, Khalid A. Saeed (2008)
Exact reliability evaluation of large size complex networks becomes intractable with conventional techniques due to the exponential scaling of the computation complexity as the size of network scales up. In this paper we develop a scalable model for the exact evaluation of system reliability of scalable complex networks of the n-tuple bridge type based on scaled delta-star conversion. The number of steps as well as the computation overhead is kept within practical limits as they scale up linearly with the size of the network. The proposed model enables simple numerical evaluation either manually or through spread-sheets.